The impact of the strategic learning achievement program in primary education students in Arequipa - Castro-Cuba-Sayco, S.E., (2019)
This work aims to determine the relation of the results of the Peruvian national assessment of students that finish the third cycle of compulsory education in the area of mathematics and the knowledge and development of abilities considered at second level in the national assessment of students by the elementary teachers of nine schools under feedback-based monitoring by the Strategic Learning Achievement Program in the Local Educational Management Unit of South Arequipa. According to the results obtained, there is a high correlation between the Educational Quality Exam results and the results of the teachers’ test and the observation form applied to the teachers. In light of the results, it is found that the ignorance of the prioritized skills of mathematics in the Peruvian national assessment and the deficient application of strategies by the teacher influences the low results in learning achievements of students who finish compulsory education. The research concludes that the high correlation (0.9) between the strategies used by the teacher to develop skills prioritized by the census evaluation, in the area of Mathematics, and the number of students.